Enlightening Minds: Promoting Education through Buddhist Principles in India - Dr.Gedam. Kamalakar; Dr. Kandi Kamala (International Journal of Educational Excellence and Innovation, 2025)
The goal of Buddhist education is to transform the personality into the highest form of humanity through moral, intellectual and spiritual perfection. These three abilities which complete human life undoubtedly lead man through worldly happiness to supramundane happiness which is the highest achievement that we all seek equally. Education is taught or expected to shape the character of a society. This article tries to discuss the teachings of Buddhism in ancient India. It is well known that the rise of Buddhism in India ushered in the golden age of Indian culture and civilization. The rise of Buddhism in India led to the establishment of many centers of learning that did not exist before. Buddhist education brought revolutionary changes in society. We still remember the glory of Nalanda University, Vikramshila University, Sonepuri University, Salwan University, Jagadhar University, Pandit Vihar University, Taxila University etc. This article also emphasizes the important role of Buddhist monasteries in promoting education in India and other Asian countries.